Manufacturing of biomaterials with engineered porosity for the promotion of osseointegration : biocompatible duplex cpating on titanium alloy for hard tissie replacement - Ng, Boon Sing (2008)
Potential nickel ion release from nickel-titanium alloy (NiTi) in physiological fluid environment has hindered the alloy's medical application thus far. Even Ti6A14V, an established implant material, is known to release metallic ions in-vitro and in-vivo. To improve its biocompatibility, metal concentration at the surface was minimized by etching. A duplex titanium oxide, calcium phosphate (TiO/CaP) coating was the depostied by anodsng NiTi, Ti6A14V in a suitable electrolyte and subsequent imersion in simulated body fluid with three times the standard ion concentration (SBFx3). X-ray photoelectron spectroscopy (XPS) study indicates that anodic titanium oxide has thicker top TiO2 layer than those formed in air. Thickness of the dioxide layer increases with anodising coltage. Mixtures of titanium sub-oxides exist between the TiO2 and the metal substrate for all samples. The lack of typical titanium pcide (rutile, anatase) peaks during thin-film x-ray difraction (TF-XRD) analysis shows that titanium oxide formed is amorphous in nature, or with poorly ordered crystal structures of size beyond the sensitivity of the instrument.